Propylene and butylene glycol: new alternatives to ethylene glycol in conjugated polymers for bioelectronic applications. Issue 3 (22nd December 2021) - Moser, Maximilian; Wang, Yazhou; Hidalgo, Tania Cecilia; Liao, Hailiang; Yu, Yaping; Chen, Junxin; Duan, Jiayao; Moruzzi, Floriana; Griggs, Sophie; Marks, Adam; Gasparini, Nicola; Wadsworth, Andrew; et al.
Abstract : Propylene and butylene glycol oligoether chains have been employed as alternatives to ethylene glycol in thiophene based semiconductors for OECTs. Their impact on electrochemical, microstructure, and swelling properties are discussed. Abstract : To date, many of the high-performance conjugated polymers employed as OECT channel materials make use of ethylene glycol (EG) chains to confer the materials with mixed ionic-electronic conduction properties, with limited emphasis placed on alternative hydrophilic moieties. While a degree of hydrophilicity is required to facilitate some ionic conduction in hydrated channels, an excess results in excessive swelling, with potentially detrimental effects on charge transport. This is therefore a subtle balance that must be optimised to maximise electrical performance. Herein a series of polymers based on a bithiophene–thienothiophene conjugated backbone was synthesised and the conventional EG chains substituted by their propylene and butylene counterparts. Specifically, the use of propylene and butylene chains was found to afford polymers with a more hydrophobic character, thereby reducing excessive water uptake during OECT operation and in turn significantly boosting the polymers' electronic charge carrier mobility. Despite the polymers' lower water uptake, the newly developed oligoether chains retained sufficiently high degrees of hydrophilicity to enable bulk volumetric doping, ultimately resulting in the development of polymers with superior OECT performance.